Nature of Particular Structure Position of the Antarctica - Pavlenkova, N.I. (Український антарктичний журнал, 2009)
Two specific structural features are typical for the Antarctica continent. These are its position in the South Pole area with strong symmetry relatively the Arctic Ocean, and a system of the oceanic ridges forming a ring around Antarctica with regular sprigs of mid-oceanic ridges. The origin of these regular structures is difficult to conform to chaotic movement of the lithosphere plates but it may be explained by the fluids-rotation conception proposed by the author. The conception supposes two main energy sources of the global tectonics: the degasification of the Earth (the fluids advection) and changes in the Earth rotation. Three basic stages of the tectonosphere formation are distinguished by the conception. Judging by the paleomagnetic data in Archean- Proterozoi several blocks of thick continental lithosphere were formed in the southern hemisphere. Geochemical studies show that the continental lithosphere was formed in from the mantle matter with large contents of fluids and it means that the intensive deep fluid flow has been at that time in the southern hemisphere. The formation of the thick lithosphere has led to asymmetry of a planet and to the relative displacement of the mass centers of the Earth's spheres. That resulted in turning of the mantle around the core in Paleozoic with movement of the continental hemisphere to the north. Rotation of the mantle around the core created a new no equilibrium system. Therefore in Mesozoic era an expansion of the southern hemisphere began. Such expansion created the regular system of the mid-oceanic ridges forming a ring around Antarctica. Supposedly at the last stage the formation of the Antarctica continent on South Pole and destruction of a continental crust on the northern hemisphere (formation of the Arctic Ocean) took place to mount on the mass center balance. Две специфические структурные особенности характерны для континента Антарктида. Это – его положение на Южном полюсе, строго симметричное относительно Арктического океана, и наличие окружающего континент кольца океанических рифтов с ответвляющимися от него срединно-океаническими хребтами. Формирование этих регулярных структурных особенностей трудно согласовать с хаотичным движением литосферных плит, но достаточно строго может быть описано с позиций предложенной автором ротационно-флюидной концепции. По этой концепции существуют два главных источника энергии глобальной геодинамики: дегазация Земли (флюидная адвекция) и изменения в характере вращения Земли. Выделяются три основные стадии развития тектоносферы. В архее и протерозое несколько крупных континентов сформировалось по палеомагнитным данным в Южном полушарии. По геохимических данным известно, что формирование континентальной литосферы происходит из мантийного вещества, насыщенного флюидами, следовательно, в это время максимальный поток глубинных флюидов был в Южном полушарии. Образование мощной континентальной литосферы должно было привести к асимметрии планеты и к относительному смещению центров масс земных сфер. Для восстановления равновесия в палеозое началось вращение мантии вокруг ядра и перемещение континентальных масс на север. Но это перемещение создало новую неравновесную систему. В результате в мезозое началось расширение Южного полушария. Это расширение привело к формированию регулярной системы срединно-океанических хребтов,образующих кольцо вокруг Антарктиды. На последней стадии развития восстановление баланса масс осуществляется за счет роста континента Антарктиды в южном полушарии и разрушения земной коры Арктики.